Spatial Activity and Labour Market Patterns - Giovanni Russo; Aura Reggiani; Peter Nijkamp (Tinbergen Institute, 2005)
The spatial activity patterns of firms in a multi-regional system are closely connected with the structure and evolution of regional labour markets. Based on an extensive data set (cross-section) on commuting flows in Germany, this paper aims to identify the relationship between entrepreneurial activity and spatial labour markets, by employing in particular the concept of 'entrepreneurial city'. A network connectivity model is adopted to assess connectivity patterns, using the power-law and exponential law as a statistical test framework, in order to detect the presence of economic activity hubs that may resemble the concept of entrepreneurial cities. Various results are presented and interpreted in the final part of the paper.
Keywords: O30; 330; Network; Commuting; Entrepreneurship; Regionaler Arbeitsmarkt; Internalisierung externer Effekte; Unternehmensgründung; Schätzung; Deutschland